ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio